Analisis Flypaper Effect dan Implikasinya Terhadap Kemandirian Fiskal Daerah: Efek Moderasi Upaya Pajak - Dewi, Nyoman Ayu Wulan Trisna; Dewi, Luh Gede Kusuma; Wiguna, I Gd Nandra Hary (Program Studi Akuntansi Fakultas Ekonomi dan Bisnis Universitas Mahasaraswati Denpasar, 2024)
This study aims to analyze the flypaper effect phenomenon in Bali Province and its implications for regional fiscal independence. Furthermore, this research also examines the role of local tax efforts in the relationship between the flypaper effect and the regional fiscal independence of the regional government of Bali Province. It is hoped that the results of this research will provide implementation for regional governments in formulating policies that support the realization of fiscal decentralization in regional governments so that they are able to achieve regional financial independence and the effectiveness of PAD as a form of regional government fiscal performance. This research uses secondary data from the APBD of Regency/City Regional Governments throughout Bali Province from 2019–2022, obtained from dpjk.kemenkeu.go.id and bps.go.id. This research uses a multiple regression analysis approach and moderated regression (MRA). The results of this research indicate that the flypaper effect phenomenon occurs in the regional government of Bali province. The flypaper effect phenomenon has been proven to have a negative influence on regional fiscal independence; however, tax efforts are a homologizer moderator of the relationship between the flypaper effect and fiscal independence.